Predominantly Fibrous Malignant Mesothelioma in a Cat - Alexander Th. A. Weiss; Afonso B. da Costa; Robert Klopfleisch (Veterinary Medicine International)
Malignant mesotheliomas are rare tumours in domestic cats. They occur within the abdominal or thoracic cavity and are regularly associated with pleural or peritoneal effusions. The histopathological diagnosis can be quite challenging, as these neoplasms may resemble other epithelial or mesenchymal neoplasms. However, differentiation can be achieved by immunohistochemistry in most cases. Here we describe the rare case of a malignant mesothelioma of the fibrous subtype in the thoracic cavity of a cat and discuss differential diagnoses and treatment options for this tumor type.